O professor surdo e a formação acadêmica de alunos no ensino superior: desafios e possibilidades - Morais, Creudimar da Silva (2022)
The objective of the present research is to understand the daily life of the deaf teacher, their didactics, their interpersonal relationships and their own protagonism, within the educational context. As specific objectives, the research proposes to: deepen the specific legislation for the training and work of the deaf teacher to reflect on the prejudice against the deaf teacher; to value the training of deaf teachers as important in teaching and to discuss Human Rights - universal access to education (LBI, PNE) and Public Inclusion Policies, which regulate the education of deaf students and the importance of including deaf teachers. Decree No. 5,626 of 2005 will also be analyzed due to its importance for the autonomy of the deaf teacher in the context of education, as well as the Law of quotas and the presence of the deaf teacher in federal public education. This research seeks to analyze the prejudice against the deaf person in the context of education and the empathy of students in relation to the deaf teacher, as well as the specificities of the training of deaf teachers. Building a culture of peace is essential for expanding multiculturalism and tolerance for individual differences. (AU)